(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept of "Homeland" (Patria) is deeply rooted in cultural identity and emotional resonance in the Spanish-speaking world. Through aphorisms and proverbs, this concept is expressed in ways that reveal the values, historical experiences, and emotional connections of Spanish communities. This study explores the linguistic and cultural features of the term "Homeland" as reflected in Spanish aphorisms and proverbs. It identifies recurring themes such as sacrifice, pride, emotional attachment, and collective identity. Using a corpus of widely known Spanish proverbs and aphorisms, the study employs qualitative analysis to examine their structure, semantics, and cultural implications.